180 mW, 1 MHz, 15 fs carrier-envelope phase-stable pulse generation via polarization-optimized down-conversion from gas-filled hollow-core fiber - Srivastava, Anchit; Scheffter, Kilian; Jun, Soyeon; Herbst, Andreas; Fattahi, Hanieh (Applied Physics Letters, 2024)
Gas-filled hollow core fibers allow the generation of single-cycle pulses at megahertz repetition rates. When coupled with difference frequency generation, they can be an ideal driver for generating carrier-envelope phase stable, octave-spanning pulses in the short-wavelength infrared. In this work, we investigate the dependence of the polarization state in gas-filled hollow-core fibers (HCF) on the subsequent difference frequency generation stage. We show that by adjusting the input polarization state of light in geometrically symmetric systems, such as hollow-core fibers, one can achieve precise control over the polarization state of the output pulses. This manipulation preserves the temporal characteristics of the generated ultrashort pulses, especially when operating at a near single-cycle regime. We leverage this property to boost the downconversion efficiency of the near single-cycle pulses in a type I difference frequency generation stage. Our technique overcomes the bandwidth and dispersion constraints of the previous methods that rely on broadband waveplates or adjustment of crystal axes relative to the laboratory frame. This advancement is crucial for experiments demanding pure polarization states in the eigenmodes of the laboratory frame.
CRIS-Team Scopus Importer:2024-11-29

Multi-modal field-resolved spectroscopy at near-petahertz frequencies - Scheffter, Kilian; Srivastava, Anchit; Herbst, Andreas; Jun, Soyeon; Fattahi, Hanieh (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
We present multi-modal field-resolved detection of stimulated Raman, overtone, and combination bonds at near-petahertz frequencies. We successfully resolve the Raman resonance of the CN stretching, CH stretching, and CH3 deformation bond of liquid acetonitrile while observing linear absorption of atmospheric water present in the ambient.
CRIS-Team Scopus Importer:2025-04-25
Keywords: femtosecond fieldoscopy; field-resolved spectroscopy; stimulated Raman spectroscopy

Near-Petahertz Femtosecond Fieldoscopy: A Leap in Liquid Phase Spectroscopy - Srivastava, Anchit; Herbst, Andreas; Tani, Francesco; Fattahi, Hanieh (2023 IEEE Photonics Conference, IPC 2023 - Proceedings, 2023)
Overtone and combination bands of aqueous water molecules are resolved with unprecedented detection sensitivity at 1.34 μmol. This was accomplished via a bright frontend delivering synchronized 4.8 fs pulses at 1 μm, and phase-stable 17 fs pulses at 2 μm, combined with near-petahertz electro-optic sampling.
CRIS-Team Scopus Importer:2024-12-16
Keywords: aqueous solution; femtosecond fieldoscopy; field-resolved spectroscopy; NIR spectroscopy; ultrashort pulse generation

Near-petahertz fieldoscopy of liquid - Srivastava, Anchit; Herbst, Andreas; Bidhendi, Mahdi M.; Kieker, Max; Tani, Francesco; Fattahi, Hanieh (Nature Photonics, 2024)
Measuring transient optical fields is pivotal not only for understanding ultrafast phenomena but also for the quantitative detection of various molecular species in a sample. Here we demonstrate near-petahertz electric field detection of a few femtosecond pulses with 200 attosecond temporal resolution and subfemtojoule detection sensitivity. By field-resolved detection of the impulsively excited molecules in the liquid phase, termed femtosecond fieldoscopy, we demonstrate temporal isolation of the response of the target molecules from those of the environment and the excitation pulse. In a proof-of-concept analysis of aqueous and liquid samples, we demonstrate field-sensitive detection of combination bands of 4.13 μmol ethanol for the first time. This method expands the scope of aqueous sample analysis to higher detection sensitivity and dynamic range, while the simultaneous direct measurements of phase and intensity information pave the path towards high-resolution biological spectro-microscopy.
CRIS-Team Scopus Importer:2024-11-01

Nonlinear dynamics of femtosecond laser interaction with the central nervous system in zebrafish - Jun, Soyeon; Herbst, Andreas; Scheffter, Kilian; John, Nora; Kolb, Julia; Wehner, Daniel; Fattahi, Hanieh (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
Understanding the photodamage processes driven by the complex nonlinear interactions of femtosecond laser pulses within the second tissue transparency window is pivotal for developing novel label-free microscopy techniques. In this research, we identify two distinct cavitation mechanisms produced by 1030 nm femtosecond pulses in the zebrafish central nervous system. The damage remains highly localized for irradiation at lower laser repetition rates, resulting from plasma-induced ablation and localized heating. In contrast, higher laser repetition rates lead to more extensive damage mediated by plasma-induced photochemical reactions. We also investigate how fluorescence labels, involving both linear and nonlinear absorption pathways, influence the dynamics of the photodamage. To confirm our findings, we analyzed cell death and tissue responses to laser-induced injury, including the activation of fibroblasts and the recruitment of immune cells.
CRIS-Team Scopus Importer:2025-05-16
Keywords: central nervous system; deep-tissue imaging; femtosecond pulses; light tissue interaction; photodamage; photothermal damage; phototoxicity; reactive oxygen species; zebrafish

Nonlinear dynamics of femtosecond laser interaction with the central nervous system in zebrafish - Jun, Soyeon; Jun, Soyeon; Herbst, Andreas; Herbst, Andreas; Scheffter, Kilian; John, Nora; Kolb, Julia; Wehner, Daniel; Fattahi, Hanieh (Communications Physics, 2024)
Understanding the photodamage mechanism underlying the highly nonlinear dynamic of femtosecond laser pulses at the second transparent window of tissue is crucial for label-free microscopy. Here, we report the identification of two cavitation regimes from 1030 nm pulses when interacting with the central nervous system in zebrafish. We show that at low repetition rates, the damage is confined due to plasma-based ablation and sudden local temperature rise. At high repetition rates, the damage becomes collateral due to plasma-mediated photochemistry. Furthermore, we investigate the role of fluorescence labels with linear and nonlinear absorption pathways in optical breakdown. To verify our findings, we examined cell death and cellular responses to tissue damage, including the recruitment of fibroblasts and immune cells after irradiation. These findings contribute to advancing the emerging nonlinear optical microscopy techniques and provide a strategy for inducing precise, and localized injuries using near-infrared femtosecond laser pulses.
CRIS-Team Scopus Importer:2024-05-31

Octave-spanning, field-resolved, Kerr-amplification in liquid thin film - Scheffter, Kilian; Srivastava, Anchit; Herbst, Andreas; Jun, Soyeon; Fattahi, Hanieh (Proceedings of SPIE - The International Society for Optical Engineering, 2025)
We demonstrate octave-spanning amplification of ultrashort pulses at megahertz repetition rates via Kerr instability amplification in a thin liquid acetone film. We directly resolve and characterize the electric field of all the newly generated photons via various third-order processes occurring in the liquid film.
CRIS-Team Scopus Importer:2025-05-16
Keywords: femtosecond fieldoscopy; high repetition rate single cycle sources; Kerr instability amplification; Single-cycle pulse amplification